2022
DOI: 10.1017/s0007114522000265
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammation index and osteoarthritis in the elderly: is there a mediating role of physical activity?

Abstract: Objective: This study examined whether physical activity (PA) explains the association between dietary inflammatory potential and OA in the elderly. Methods: A total of 1249 elderly people (≥65 years) were eligible for this study from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016. The semi-quantitative Food Frequency Questionnaire (FFQ) and Global PA Questionnaire (GPAQ) were used to evaluate the diet and PA of the elderly, respectively. The multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
13
2
Order By: Relevance
“…The present study failed to detect significant associations between E-DII scores and CV loss and BML size increase, except for medial tibial BML increase over 10.7 years. These findings appear to be contrary to two cross-sectional studies that found the DII scores to be associated with prevalent and symptomatic KOA 15,24 and a 48-month follow-up study showing DII scores to be related to incident ROA. 25 Veronese et al found that participants with higher DII scores had a higher prevalence of radiographic symptomatic KOA compared to those consuming a more anti-inflammatory diet, indicated by a lower DII score.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study failed to detect significant associations between E-DII scores and CV loss and BML size increase, except for medial tibial BML increase over 10.7 years. These findings appear to be contrary to two cross-sectional studies that found the DII scores to be associated with prevalent and symptomatic KOA 15,24 and a 48-month follow-up study showing DII scores to be related to incident ROA. 25 Veronese et al found that participants with higher DII scores had a higher prevalence of radiographic symptomatic KOA compared to those consuming a more anti-inflammatory diet, indicated by a lower DII score.…”
Section: Discussioncontrasting
confidence: 99%
“…15 A cross-sectional association between E-DII scores and selfreported OA was reported using data from 1,249 older adults in the National Health and Nutrition Examination Survey (NHANES), and this association was partially mediated by physical activity. 24 Liu et al found that the highest E-DII score quartile was associated with a higher incidence of radiographic and symptomatic KOA over 48-month follow-up period, and these associations were mediated by BMI. 25 The discrepancies between our study and the crosssectional studies may be due to differences in participants' characteristics, knee structure assessment, and study design and/or variations in the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary intake was assessed from a single 24-h dietary recall in NHANES. It contains 27 dietary ingredient or nutrient parameters used to calculate the E-DII or DII score, including carbohydrates, protein, fat, cholesterol, (saturated, monounsaturated and polyunsaturated) fatty acids, omega-3 and omega-6 polyunsaturated fatty acids, vitamins (A, B1, B2, B6, B12, C, D, E), niacin, iron, magnesium, zinc, selenium, folic acid, beta carotene, alcohol, fiber and caffeine ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The higher the absolute value of DII, the stronger the effect of diet on inflammation. DII has been reported to strongly correlate with many chronic diseases, such as coronary heart disease [ 18 ], metabolic syndrome [ 19 ], cancer [ 20 ], and osteoarthritis [ 21 ]. Studies demonstrated that a low DII diet was related to improved BMD in postmenopausal women of different races [ 22–24 ].…”
Section: Introductionmentioning
confidence: 99%